Perancangan Aplikasi Pembelajaran Pengenalan Nama Benda 3 Bahasa (Arab, Inggris, Mandarin) Berbasis Android Menggunakan Metode Prototype (Studi Kasus: Paud Daar El Hasanah) - Nur Afifah; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Language is the most important means of communication for humans, since it serves as a means of conveying messages from a person to others. One of the popular languages among Indonesians is English and Arabic. Language learning in the conventional way is usually carried out in a face-to-face manner directly with teachers at school or in science assemblies. The existence of mobile-based technology that is currently popular, namely Android, can help the language learning process, so that English and Arabic learning can be poured into digital forms. Introducing objects to children from an early age is very necessary to help the growth and development of children so that they have readiness to enter further education, especially at the kindergarten level, to be more mentally prepared when entering the elementary school level. The problem that often arises is that when learning children tend to be bored due to the lack of learning media used as material delivery. This has led to a decrease in interest in learning in children. To overcome these problems, PAUD DAAR EL HASANAH Kindergarten requires learning media that can help students in learning to be more fun. So with that, researchers are interested in designing an android-based 4 language object recognition application (Indonesian, Arabic, English, Mandarin), with the hope that the application can help students in learning. The application was designed using Construct 2 and tested using the black box method. The content of this application displays material on the introduction of objects in 4 languages, namely Indonesian, Arabic and English on different menus, there is also a play menu such as a quiz to hone children's skills. With an attractive appearance, this application helps teachers in the learning process, as well as parents in the learning process of children at home. Before testing, a demo of the application was carried out first so that parents and students understood how to use the application, which then students tried the application accompanied by teachers and parents. From the results of tests and questionnaires from 40 respondents who stated that the application is suitable for use as a learning medium, especially to introduce objects.